Circ_0007331 knock‐down suppresses the progression of endometriosis via miR‐200c‐3p/HiF‐1α axis - Dong, Lan (J Cell Mol Med, 2020)
Endometriosis is considered a benign gynaecological disease with cancer‐like characterizations, which has a high incidence among women of reproductive age. However, this disease has so far lacked timely diagnosis and effective treatment owing to its unclear aetiology. In this study, we identified aberrant high expression of circ_0007331 in ectopic endometrial cells by comparing the endometrial samples from patients with and without endometriosis. Further functional experiments revealed that circ_0007331 knock‐down effectively suppressed the viability, proliferation and invasive capacity of ectopic endometrial cells. Additionally, we attempted to define the molecular mechanism of circ_0007331 in the initiation and progression of endometriosis. Circ_0007331 acted as a miRNA sponge for miR‐200c‐3p to indirectly regulate the function of HIF‐1α, which plays a key role in the local angiogenesis and hypoxic mechanisms of ectopic endometrium. A final in vivo experiment confirmed that circ_0007331 knock‐down could suppress the development of endometriosis through down‐regulating the expression of HIF‐1α. Collectively, we preliminarily characterized the role and possible insights of circ_0007331/miR‐200c‐3p/HIF‐1α axis in the proliferation and invasion of ectopic endometrial cells. We hope that by exploring the potential function and molecular mechanism of circ_0007331, we can increase our biological insight into the pathogenesis of endometriosis, which will bring the new ways for the diagnosis and therapy of this disease.